Profil Pemberian Vaksin Rabies pada Pasien Digigit Anjing di Puskesmas Natarandang, Kecamatan Wolomeze, Nusa Tenggara Timur, Indonesia: Penelitian - Natalia Ginting, Sri (PT Kalbe Farma Tbk., 2026)
Introduction: Rabies is a viral disease that is almost always fatal once clinical symptoms appear, with dogs being the primary source of transmission. This study aims to describe the rabies vaccination profile of dog bite patients at Natarandang Health Center, Wolomeze District. Methods: A retrospective descriptive study on 32 patients who received rabies vaccination after dog bites between January 2022 and February 2023. Data were collected from medical records and analyzed descriptively. Results: Most patients were male (65.6%), with the most common bite locations in the calf (34.4%) and hand (28.1%). The most frequent first aid measures included checking the dog's infection history and seeking medical attention (34.4% each). The most commonly administered rabies vaccine was PCECV (81.3%). Delayed medical care was associated with fever (65.6%) as the predominant symptom. Conclusion: Most dog bite patients at Natarandang Health Center were male, with the most common bite locations in the calf and hand. The most frequently reported first aid were checking the dog’s history and seeking medical attention. The predominant rabies vaccine administered was PCECV. Fever was the most common symptom.